Asuhan Keperawatan Pada An.M Dengan Kejang Demama Di Ruang Mawar Rsud Banyudono - Wibisono, Afif; , Irdawati S. Kep., Ns, Msi. Med (2015)
Background: Febrile seizure is a neurological disorder that is most commonly found in children, because of the rise of febrile seizures associated with age, level of temperature and speed of temperature increase, including hereditary factors also have a role in the rise of febrile seizures where the patient's family members have the opportunity to experience seizures more than the normal children. febrile seizures are seizures that occur due to the increase in body temperature (rectal temperature over than 38oC), due to a process extra cranium. Method: The author uses the method of description, while the sample is An M, the data obtained by ways: interview, examination, activities observation, obtaining records and diagnostic reports, cooperates with friends. Results: After the act of nursing for 3 days diagnoses that appeared three are: hyperthermia associated with the disease, impaired nutritional needs: less than body requirements related to the inadequate intake, the risk of recurrent seizures associated with hyperthermia. Conclusion: Cooperation between the health team and the patient or family is indispensable for the success of nursing care to patients so that the patients nursing problems regarding hyperthermia need nutrition: less than body requirements, the risk of recurrent seizures can be executed properly and the problem can be resolved in part. Keywords: Seizures Fever, hyperthermia, nutritional deficiencies.